2018
DOI: 10.3168/jds.2017-13719
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition before and after 6 months of age in Holstein-Friesian bulls: I. Effects on performance, body composition, age at puberty, and postpubertal semen production

Abstract: The aim of this study was to examine the effect of plane of nutrition (1) during the first 6 mo of life and (2) from 6 mo of age to puberty on early growth characteristics, age at puberty, and postpubertal semen production in Holstein-Friesian bulls. Holstein-Friesian bull calves (n = 83) with a mean (standard deviation) age and body weight of 17 (4.4) d and 52 (6.2) kg, respectively, were assigned to a high (Hi) or low (Lo) plane of nutrition for the first 6 mo of life. The Hi and Lo calves received 1,200 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
(62 reference statements)
5
31
0
Order By: Relevance
“…We have reported that increasing consumption of commercial milk replacer in suckling Holstein bull calves leads to an overall increase in body growth with improved feed e ciency, and speci c changes in growth rates of abdominal organs and tissues [9]. Improved body, carcass and ST muscle weights at 42 days of age in calves on a higher plane of nutrition in this study (Table 2) supports the work of Byrne et al [2] and others [11,1]. While the increased body weight gain is not always sustained into adulthood, suckling bull and heifer calves on a higher plane of nutrition reach puberty at an earlier age and producers see an economic advantage over later maturing livestock.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We have reported that increasing consumption of commercial milk replacer in suckling Holstein bull calves leads to an overall increase in body growth with improved feed e ciency, and speci c changes in growth rates of abdominal organs and tissues [9]. Improved body, carcass and ST muscle weights at 42 days of age in calves on a higher plane of nutrition in this study (Table 2) supports the work of Byrne et al [2] and others [11,1]. While the increased body weight gain is not always sustained into adulthood, suckling bull and heifer calves on a higher plane of nutrition reach puberty at an earlier age and producers see an economic advantage over later maturing livestock.…”
Section: Discussionsupporting
confidence: 87%
“…An increased plane of nutrition in the preweaning period can promote growth in replacement heifers so that they reach puberty and calve at an earlier age; and produce more milk at rst lactation [1]. Bull calves on a high plane of nutrition in their rst six months of life reached puberty at an earlier age than bull calves on a low plane of nutrition [2] and this hastened the availability of salable semen. Beef cattle on a higher plane of nutrition in the preweaning period enter the feedlot at an earlier age and gain weight more e ciently than older aged cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The management of the bulls has been described in detail (Byrne et al, 2018a). Diets were designed using National Research Council (NRC) guidelines (2001).…”
Section: Animals and Semen Collectionmentioning
confidence: 99%
“…Enhanced pre-pubertal nutrition elevates the percentage of progressively motile and upregulates mitochondrial function in sperm of post-pubertal dairy bulls ( Johnson et al, 2020 ). In contrast, low planes of nutrition of young Holstein-Friesian bulls resulted in the retarded onset of puberty ( Byrne et al, 2018 ). Although epigenetic studies related to bull metabolic status is still missing, DNA methylation and histone modifications patterns were both reported to be associated with bull fertility ( Verma et al, 2015 ; Kropp et al, 2017 ; Kutchy et al, 2018 ; Capra et al, 2019 ; Ugur et al, 2019 ).…”
Section: The Known Non-genetic Parental Influences In Dairy Cattlementioning
confidence: 99%